The implementation of a story-based module to improve students’ learning outcomes: A needs analysis study (Lighthouse Publishing, 2022)
This study aims to analyze the needs of students for teaching materials that are creative, innovative and in accordance with the level of development of students. Module based on picture story can assist students to understand the material and improve cognitive learning outcomes. The study was undertaken at SD Negeri Berundung, Ketapang District, South Lampung Regency with a total sample of 28 students. Data collection was undertaken by distributing questionnaires to students. There are several aspects that become references in making the questionnaire, namely regarding the learning that has been carried out, the use of teaching materials used during offline and online learning, interest in picture story-based modules, strategies and methods used by educators in learning. The results of the data were analyzed by calculating the percentage, besides being presented in the form of a percentage, descriptive analysis was also undertaken. The analysis has indicated how interested students are in the picture story-based module and the picture story-based module analysis was the needs of students in the learning process. Dealing with the results of the study, students needed teaching materials in the form of modules based on picture story to facilitate learning and improve students’ cognitive learning outcomes during the Covid-19 pandemic.